Bioslurry as a fuel. 5. Fuel properties evolution and aging during bioslurry storage - Zhang, Mingming; Liaw, Sui Boon; Wu, Hongwei (American Chemical Society, 2013)
This study investigates the evolution of fuel properties and aging of a series of bioslurry fuels prepared from fast pyrolysis bio-oil and biochar at different biochar loading levels (up to 20 wt %) for a storage period of 29 days. The results demonstrate that, at room temperature, the storage of bioslurry results in a reduction in the acidity [total acid number (TAN)], a reduction in the viscosity, and an increase in the water content of the bio-oil phase. In comparison to the blank bio-oil samples, the presence of biochar leads to more severe changes in the fuel properties of bioslurry. After 29 days of storage, the bioslurry fuels are still acidic. An increase in the biochar loading level further decreases the TAN and viscosity of bio-oil phases and increases the water content of bio-oil phases. The storage of bioslurry also results in undesired redistribution of alkali and alkaline earth metallic species between the biochar and bio-oil phase in bioslurry, via the leaching of these inorganic species from the biochar into the acidic bio-oil by two-step kinetics.